2017
DOI: 10.1371/journal.pone.0173766
|View full text |Cite
|
Sign up to set email alerts
|

The distinct plastid genome structure of Maackia fauriei (Fabaceae: Papilionoideae) and its systematic implications for genistoids and tribe Sophoreae

Abstract: Traditionally, the tribe Sophoreae sensu lato has been considered a basal but also heterogeneous taxonomic group of the papilionoid legumes. Phylogenetic studies have placed Sophoreae sensu stricto (s.s.) as a member of the core genistoids. The recently suggested new circumscription of this tribe involved the removal of traditional members and the inclusion of Euchresteae and Thermopsideae. Nonetheless, definitions and inter- and intra-taxonomic issues of Sophoreae remain unclear. Within the field of legume sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
(90 reference statements)
4
30
0
Order By: Relevance
“…Of note, the IV-D is a synapomorphy of one subclade of the tribes Phaseoleae and core-Millettieae, which is congruent with their closely related evolutionary relationships. Consistent with some previous studies (Martin et al, 2014;Dugas et al, 2015;Choi and Choi, 2017), our results suggest that significant plastome structural rearrangements such as inversion may provide useful information about phylogenetic relationships. However, some previous studies have suggested caution in using inversions in phylogenetic analysis.…”
Section: Insights Into the Plastomic Evolution Of The Mp Cladesupporting
confidence: 92%
See 3 more Smart Citations
“…Of note, the IV-D is a synapomorphy of one subclade of the tribes Phaseoleae and core-Millettieae, which is congruent with their closely related evolutionary relationships. Consistent with some previous studies (Martin et al, 2014;Dugas et al, 2015;Choi and Choi, 2017), our results suggest that significant plastome structural rearrangements such as inversion may provide useful information about phylogenetic relationships. However, some previous studies have suggested caution in using inversions in phylogenetic analysis.…”
Section: Insights Into the Plastomic Evolution Of The Mp Cladesupporting
confidence: 92%
“…Most members of papilionoids, with the exception of a few early diverging lineages, share a 50-kb inversion in the LSC (Doyle et al, 1996). Previous studies have reported multiple inversions of 23, 24, or 36-kb in the Genistoid clade (Martin et al, 2014;Choi and Choi, 2017;Feng et al, 2017;Keller et al, 2017), a 39kb inversion in Robinia (Schwarz et al, 2015), and a large 78-kb inversion in the subtribe Phaseolinae of tribe Phaseoleae (Bruneau et al, 1990). However, only a few studies have examined PSV in the Millettioid/Phaseoloid clade (hereafter referred as the MP clade), one of the most species-rich clades within subfamily Papilionoideae.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Chloroplast genome structure and gene order are also highly affected by inversions. Many inversions have been described in the literature, especially in legumes, with, for instance, fragments of 50 kb in the Papilionoideae [38], 36 kb in the Genistoids [39]; 29 kb in Sophoreae [40] or 7 kb in Tylosema esculentum [41]. Multiple inversions have also been found in Geraniaceae, Campanulaceae (more than 40 inversions detected), and other lineages [25,42,43].…”
Section: Structural Evolutionmentioning
confidence: 99%